Disease-Modifying Effect of Anthraquinone Prodrug with Boswellic Acid on Collagenase-Induced Osteoarthritis in Wistar Rats - Suneela, Dhaneshwar; Dipmala, Patil; Abhay, Harsulkar; Prashant, Bhondave (Inflammation & Allergy-Drug Targets (Discontinued), 2013)
Diacerein and its active metabolite rhein are promising disease modifying agents for osteoarthritis (OA). Boswellic acid is an active ingredient of Gugglu; a herbal medicine commonly administered in osteoarthritis. Both of them possess excellent anti-inflammatory and anti-arthritic activities. It was thought interesting to conjugate rhein and boswellic acid into a mutual prodrug (DSRB) and evaluate its efficacy on collagenase-induced osteoarthritis in rats wherein the conjugate, rhein, boswellic acid and their physical mixture, were tested based on various parameters. Oral administration of 3.85 mg of rhein, 12.36 mg of boswellic acid and 15.73 mg of DSRB which would release equimolar amounts of rhein and boswellic acid, exhibited significant restoration in rat body weight as compared to the untreated arthritic control group. Increase in knee diameter (mm), due to edema was observed in group injected with collagenase, which reduced significantly with the treatment of conjugate. The hematological parameters (Hb, RBC, WBC and ESR) and biochemical parameters (CRP, SALP, SGOT and SGPT) in the osteoarthritic rats were significantly brought back to normal values on treatment with conjugate. It also showed better anti-ulcer activity than rhein. Further the histopathological studies revealed significant anti-arthritic activity of conjugate when compared with the arthritic control group. In conclusion, the conjugate at the specified dose level of 15.73 mg/kg, p. o. (BID) showed reduction in knee diameter and it could significantly normalize the hematological and biochemical abnormalities in collagenase-induced osteoarthritis in rats. Further the histopathological studies confirmed the additive anti-arthritic effect of DSRB as compared to plain rhein.
Keywords: chondroprotective